International validation of the Turkish Inappropriate Medication use in the Elderly (TIME) criteria set: a Delphi panel study - Bahat, Gulistan; Ilhan, Birkan; Erdogan, Tugba; Oren, Meryem Merve; Karan, Mehmet Akif; Burkhardt, Heinrich; Denkinger, Michael D.; Garfinkel, Doron; Cruz-Jentoft, Alfonso J.; Morrissey, Yvonne; Onder, Graziano; Pazan, Farhad; et al. (Drugs & aging, 2021)
Explicit screening tools and implicit evaluation methods have been developed to assist healthcare professionals in the management of pharmacotherapy in older adults. As prescribing habits and locally available medications vary considerably between countries, guides tailored to the needs of specific regions may be required. We aimed to report the results of the international Delphi validation study for the Turkish Inappropriate Medication use in the Elderly (TIME) criteria set, which aims to detect inappropriate prescribing in older adults in Eastern Europe.
Published online: 13 April 2021
Gesehen am 11.01.2023